PRACTICING PPE: THE CASE OF ADAM SMITH. Issue 1 (14th June 2017) - Hanley, Ryan Patrick
Abstract: Adam Smith has long been celebrated as a polymath, and his wide interests in and contributions to each of the discrete component fields of PPE have long been appreciated. Yet Smith deserves the attention of practitioners of PPE today not simply for his substantive insights, but for the ways in which his inquiries into these different fields were connected. Smith's inquiry was distinguished by a synthetic approach to knowledge generation, and specifically to generating knowledge with applications exportable to other fields. Further, Smith's investigations of various areas of study led him to recognize patterns in and across these fields, and his sensitivity to such patterns helped guide his inquiry and render it a connected enterprise. This paper examines several of Smith's discrete inquiries in the history of astronomy, language, moral philosophy, and political economy, to show how he employed the techniques of pattern detection that he practiced in each of these inquiries to the task of generating new insights into new fields of inquiry. In so doing, Smith not only distinguished himself as an early practitioner of what we today identify with PPE, but he also provides a useful point of reference for those doing PPE today.